SISTEM PAKAR BERBASIS LOGIKA FUZZY UNTUK DETEKSI LEVEL PENYAKIT SCABIES - Muhamad Safi’i; Hanny Haryanto (CCIT Journal, 2017)
Scabies is a skin disease that is easily transmitted, either through direct contact or through intermediaries such as clothes, bed sheet, and water. The disease causes itching on the body, especially at night. Transmission of the scabies disease is very fast and can develop into an outbreak in a community. Obstacles that occur in the treatment of this disease is not all people with the disease could check it for a variety of reasons, such as too busy with work and economic limitations. This research using fuzzy Tsukamoto to develop an expert system for the detection of scabiesdisease. The use of expert systems is very important because it can be a tool to substitute the expert, the expert system is easy to use, and can make decisions in a short time. Scabies disease diagnosis process carried out by way of input symptoms that suffered by patients. Symptoms that are used as input is a scratchy, itchy location, number of lesions or spots, and an extensive history of itching or the number of infected person. The outcome of this process is the level of scabies from mild to severe